Integrating Life Cycle Costing (LCC) and Life Cycle Assessment (LCA) Model for Selection of Centralized Chilled Water Generation - Review Paper - Akbar, A. (EDP Sciences, 2017)
This paper presents a review of literature relating to Life Cycle Costing (LCC) and Life Cycle Assessments (LCA) in Gas District Cooling plant. The gas district cooling plant uses either vapour compression process or absorption process for the chilled water generation. Both processes have impacts on the economic aspects as well as the contribution to CO2 emissions; thus, integration of the cost and environmental analysis of both processes are necessary. An extensive body of literature exists on both subjects, however, there is very limited number of available literature on the integration of LCC and LCA. The purpose of this review is to find the most suitable optimization model which can integrate the LCC and LCA to provide the best decision in choosing the most cost-effective and environment-friendly system. This review assesses the literature from thirty-four journals, research papers, and case reports from the year 1995 to 2017. The result of this review shows that the goal programming methodology is the appropriate method for integrating LCC and LCA because it provides the optimal decision in choosing the most cost-effective, environment-friendly system for the chilled water generation. © The authors, published by EDP Sciences, 2017.